If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ln(1 + -4x) = -6x (1 * ln + -4x * ln) = -6x (1ln + -4lnx) = -6x Solving 1ln + -4lnx = -6x Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Combine like terms: -6x + 6x = 0 1ln + -4lnx + 6x = 0 The solution to this equation could not be determined.
| -3x+8=5x-72 | | X^4+29x^2+100=0 | | 2x+7=3x+6 | | 4w^2+7w+3=0 | | 2q^2-9q-18=0 | | 5=3x+x+9 | | -1/2=3x-1/3 | | (-12)+(-3)*(-4)= | | 7w-394w+80=11 | | x+1/2=-1/5 | | 5-7x+9x=11 | | -7x-10-7x=-52 | | 6x-17=49 | | -(4x-7)=-9 | | 79=2x+5x-5 | | 6e^3x=8 | | 7n-15=62 | | -2+2x+6x=86 | | -x-8+7x=-44 | | 16b^2c-2ac+4bc=0 | | 9y-11=0 | | -3(w+3)=5(1+w) | | 8+4*5/(-10)-2=x | | 5w-14=8w | | 6x+3+x=-53 | | 12x+14=10x-24 | | 192-8x=24x | | -7-7x=-7 | | 25=2x+5x+4 | | 7p^2+5=16p | | 8+3x=-22 | | 0.6x^2+3.6x=0 |